Triplex-forming oligonucleotides as an anti-gene technique for cancer therapy - Li, Chun; Zhou, Zunzhen; Ren, Chao; Deng, Yi; Peng, Feng; Wang, Qiongfen; Zhang, Hong; Jiang, Yuan (Frontiers in Pharmacology, 2022)
Triplex-forming oligonucleotides (TFOs) can bind to the major groove of double-stranded DNA with high specificity and affinity and inhibit gene expression. Triplex-forming oligonucleotides have gained prominence because of their potential applications in antigene therapy. In particular, the target specificity of triplex-forming oligonucleotides combined with their ability to suppress oncogene expression has driven their development as anti-cancer agents. So far, triplex-forming oligonucleotides have not been used for clinical treatment and seem to be gradually snubbed in recent years. But triplex-forming oligonucleotides still represent an approach to down-regulate the expression of the target gene and a carrier of active substances. Therefore, in the present review, we will introduce the characteristics of triplex-forming oligonucleotides and their anti-cancer research progress. Then, we will discuss the challenges in their application.